Child Justice System in ‘Uqubat Dropping of Child Sexual Abuse of Children: (Case Study of Meulaboh Syar’iyah Court Decision Number 1/JN.Anak/2022/MS.Mbo) - Fachruddin; Khalid; Yadi Harahap (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Settlement of criminal cases against children who conflict with the law must be oriented towards the principle of